Mast cell/MDSC a liaison immunosuppressive for tumor microenvironment - Danelli, Luca (Oncoimmunology, 2015)
The instauration of an immunosuppressive microenvironment is a key event in cancer development and progression. Here, we discuss increasing evidences of the crosstalk between myeloid-derived suppressor cells (MDSCs) and mast cells (MCs) as a new fuel for the cancer immunosuppressive machinery.